Comparison of ultrasound-guided lumbar plexus and sciatic nerve blocks with ropivacaine and sham blocks with saline on perianesthetic analgesia and recovery in dogs undergoing tibial plateau leveling osteotomy surgery. (September 2019) - Warrit, Kanawee; Griffenhagen, Gregg; Goh, Clara; Boscan, Pedro
Abstract: Objective: To assess the effects of ultrasound-guided lumbar plexus and sciatic nerve blocks on perianesthetic analgesia and recovery quality in dogs undergoing tibial plateau leveling osteotomy (TPLO). Animals: A group of twenty 20 dogs. Study design: Prospective, randomized, blinded, clinical study. Methods: Dogs were administered lumbar plexus and sciatic nerve blocks with ropivacaine (1.5 mg kg –1 ; group RA) or sham blocks with saline (group CON). Dogs were administered hydromorphone (0.2 mg kg –1 ) and atropine (0.02 mg kg –1 ) subcutaneously before anesthesia was induced with intravenous propofol and maintained with isoflurane. Variables included duration to perform nerve blocks, intraoperative rescue analgesia, recovery score, postoperative pain scores (modified University of Melbourne, Colorado State University and visual analog pain scales), postoperative rescue analgesia-sedation and complications observed. Two-tailed Student t test, Mann–Whitney test, repeated measures analysis of variance, Friedman test and Fisher exact test were used for comparison. Significance was p < 0.05. Results: Time to perform nerve blocks was [median (range)] 4.3 (2.6–6.1) minutes after aseptic skin preparation. Total fentanyl requirements were 14.2 ± 9 μg kg –1 and 25.4 ± 10 μg kg –1 ( p  = 0.02) and incidence of hypotension (mean arterial pressure < 60 mmHg) was 40% and 80% ( p  = 0.16) for groups RA and CON, respectively. Six of eight group CON dogs required more intensive treatment for hypotension than group RA dogs. Recovery scores were 1 (1–4) and 2.5 (1–4) for groups RA and CON, respectively ( p  = 0.04). RA dogs were less likely to require fentanyl rescue analgesia during the postoperative period ( p  = 0.04). Conclusion and clinical relevance: As part of a multimodal analgesia regimen, ultrasound-guided lumbar plexus and sciatic nerve blocks provided greater analgesia and improved recovery quality in dogs during TPLO surgery.